Tunable filter based on two cascaded photonic liquid crystal fibers - Tefelska, Marzena Maria; Ertman, Sławomir; Woliński, Tomasz; Dąbrowski, Roman; Mergo, Paweł (Photonics Letters of Poland, 2013)
This paper describes a tunable filter based on two independently tuned photonic crystal fibers (PCFs) filled with the same liquid crystal. Photonic bang-gaps (PBGs) spectral position of both PCF sections can be controlled with two separated temperature controllers. Overall transmission of the device depends on PBGs formed in both liquid crystal infiltrated PCF sections. As a result in such a cascaded device both position and bandwidth of the guided waves can be controlled. Full Text: PDF References P. St. J. Russell, "Review: Photonic Crystal Fibers", Science 299, 358-362 (2003). CrossRef C. Knight, "Photonic crystal fibres", Nature 424, 847-851 (2003). CrossRef Arismar Cerqueira S Jr, "Recent progress and novel applications of photonic crystal fibers", Rep. Prog. Phys. 73 (2010). CrossRef Larsen, T. T., Bjarklev, A., Hermann, D. S., Broeng, J., "Optical devices based on liquid crystal photonic bandgap fibres", Opt. Express 11, 2589–2596 (2003). CrossRef P. Roberts, F. Couny, H. Sabert, B. Mangan, D. Williams, L. Farr, M. Mason, A. Tomlinson, T. Birks, J. Knight, P. St. J. Russell, "Ultimate low loss of hollow-core photonic crystal fibres", Optics Express, Vol. 13, Issue 1, 236-244 (2005). CrossRef Zhang, C., Kai, G., Wang, Z., Liu, Y., Sun, T., Yuan, S., Dong, X., "Tunable highly birefringent photonic bandgap fibers". Opt. Lett. 30, 2703–2705 (2005). CrossRef Alkeskjold, T. T., Bjarklev, A. "Electrically controlled broadband liquid crystal photonic bandgap fiber polarimeter". Opt. Lett. 32, 1707–1709 (2007). CrossRef T. R. Woliński, S. Ertman, P. Lesiak, A. W. Domański, A. Czapla, R. Dąbrowski, E. Nowinowski-Kruszelnicki, J. Wójcik, "Photonic liquid crystal fibers – a new challenge for fiber optics and liquid crystals photonics", Opto-Electronics Review 14, 329-334 (2006). CrossRef Du, F., Lu, Y. Q., Wu, S. T., "Electrically tunable liquid-crystal photonic crystal fiber", Appl. Phys. Lett. 85, 2181–2183 (2004). CrossRef B. Eggleton, Ch. Kerbage, P. Westbrook, R. Windeler, A. Hale, "Microstructured optical fiber devices", Optics Express, Vol. 9, Issue 13, 698-713 (2001). CrossRef T. R. Woliński, S. Ertman, D. Budaszewski, M. Chychłowski, A. Czapla, R. Dąbrowski, A. W. Domański, P.Mergo, E. Nowinowski-Kruszelnicki, K. A. Rutkowska, M. Sierakowski, M. Tefelska, "Liquid Crystal Photonic Crystal Fibers and their applications", Proc. of SPIE Vol. 7955, (2011). CrossRef L. Scolari, T. T. Alkeskjold, A. Bjarklev, "Tunable Gaussian filter based on tapered liquid crystal photonic bandgap fibre", Electron. Lett. 42(22), 1270–1271 (2006). CrossRef M. M. Tefelska, S. Ertman, T. R. Woliński, R. Dąbrowski, J. Wójcik, "Phase shifter based on photonic liquid crystal fiber", Photonics Letters of Poland Vol 2, No 3. (2010). CrossRef M. M. Tefelska, M. S. Chychłowski, T. R. Woliński, R. Dąbrowski, J. Wójcik, "Tunable attenuation in photonic liquid crystal fibers", Photonics Letters of Poland Vol 1, No 2. (2009). DirectLink T.R. Woliński, K. Szaniawska, K. Bondarczuk, P. Lesiak, A.W. Domański, R. Dąbrowski, E. Nowinowski-Kruszelnicki, J. Wójcik, "Propagation properties of photonic crystal fibers filled with nematic liquid crystals", Opto-Electron. Rev. 13, no. 2 (2005). DirectLink R.Dąbrowski, J.Dziaduszek, Z.Stolarz, J.Kędzierski, "Liquid crystalline materials with low ordinary index", J. Opt. Technol. 72, 662-667 (2005). CrossRef T. R. Woliński, K. Szaniawska, S. Ertman, P. Lesiak, A.W. Domański, R. Dąbrowski, E. Nowinowski-Kruszelnicki, J. Wójcik, "Influence of temperature and electrical fields on propagation properties of photonic liquid crystal fibers", Meas. Sci. Technol. Vol. 17, 985–991 (2006). CrossRef